2005
DOI: 10.1158/1078-0432.ccr-04-1756
|View full text |Cite
|
Sign up to set email alerts
|

MEN4901/T-0128, a New Camptothecin Derivative–Carboxymethyldextran Conjugate, Has Potent Antitumor Activities in a Panel of Human Tumor Xenografts in Nude Mice

Abstract: Purpose: The purpose of the present study was to evaluate the antitumor activity and pharmacokinetic profile of MEN4901/T-0128 in nude mice bearing human tumor xenografts in comparison with irinotecan (CPT-11) and T-2513. Experimental Design: We have determined the antitumor activity of MEN4901/T-0128, CPT-11, and T-2513 in BALB/cA Jcl nude mice bearing human gastric (H-81), colon (H-110), lung (Mqnu-1, H-74), esophageal (H-204), liver (H-181), and pancreatic (H-48) cancer lines, which had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…In contrast, a single treatment of MEN4901/T-0128 had less effective antitumor activity unless a higher dose was used, indicating repeated treatment regimens were superior to single bolus drug administration. Furthermore, all MEN4901/T-0128 treated animals had tumor regression efficacy against the primary human colon tumor, which was consistent with antitumor activity in human tumor subcutaneous xenografts (9). …”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In contrast, a single treatment of MEN4901/T-0128 had less effective antitumor activity unless a higher dose was used, indicating repeated treatment regimens were superior to single bolus drug administration. Furthermore, all MEN4901/T-0128 treated animals had tumor regression efficacy against the primary human colon tumor, which was consistent with antitumor activity in human tumor subcutaneous xenografts (9). …”
Section: Discussionsupporting
confidence: 73%
“…T-0128 has demonstrated a strong antitumor activity against a panel of human tumor subcutaneously implanted in nude mice that were mostly refractory to CPT-11, T-2513, and topotecan (9). These studies could not evaluate antimetastatic efficacy, since they involved subcutaneously-growing tumors which do not metastasize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study in mice bearing human tumor xenografts found significant tumor inhibition at one third the MTD of 80 mg/kg once a week for four weeks (H81 gastric, 97.5%; H-110 colon, 98.5%; Mqnu-1 lung, 99.7%; H-74 lung, 90.7%; H-204 esophageal, 78.8%; H-181 liver, 81.2%; H48 pancreatic, 98.8%). 292 Pharmacokinetic evaluation of polymer bound SN-38 in nude mice bearing St-4 xenografts found plasma AUC values of 23,900 μg•h/mL and a 30 h half-life after a 40 mg/kg i.v. injection.…”
Section: Macromolecular Architectures For Passive Drug Deliverymentioning
confidence: 99%
“…On the contrary, the treatment with irinotecan and T-2513 was pharmacologically ineffective. The therapeutic treatment with the conjugate did not induce either animal death or weight loss indicating the high therapeutic index with respect to the parent drug [128].…”
Section: Camptothecinmentioning
confidence: 93%